A Blended Instructional Design for Self-Reported Historical ‎Literacy in South Asian History: Development and Initial ‎Evaluation - Septina Alrianingrum; Fadiyah Salsabila; Sumarno (JPI: Jurnal Pustaka Indonesia, 2026)
South Asian History courses often rely on dispersed, predominantly foreign-language resources that provide limited scaffolding for interpreting contested narratives and constructing evidence based historical arguments. This study developed and initially evaluated a discipline specific blended instructional package aligning synchronous guidance and asynchronous inquiry with six historical literacy indicators. Using ADDIE and an uncontrolled one-group pretest–posttest field evaluation, the study involved a convenience sample of 76 undergraduate students in three intact classes in the History Education Study Program at Universitas Negeri Surabaya. The package was designed for 16 planned sessions; however, actual instructional dosage and implementation-fidelity indicators were not systematically documented. One subject-matter validator, one media validator, and one learning validator appraised different domains using non-equivalent instruments; their domain-specific ratings ranged from 85.20% to 88.00%, with a descriptive cross-domain mean of 86.93%. Student acceptability averaged 84.82%. Aggregate self-reported historical-literacy scores increased from 51.03 (SD=14.55) to 88.93 (SD=4.91), with a mean change of 37.91, 95% CI [34.53, 41.29], t(75)=22.34, sig < .005, and Cohen’s dz = 2.56. The group-level normalized gain was 0.77 (77.39%), which was descriptively classified as high. These findings indicate high acceptability responses and substantial short term within-group gains in self-reported historical literacy. However, these findings do not establish causal effectiveness or demonstrated historical literacy performance.